The implicit beliefs and implicit behavioral tendencies towards smoking-related cues among Chinese male smokers and non-smokers - Lei Ren; Long-Biao Cui; Chen Chen; Xiaojun Dong; Zhongying Wu; Yidi Wang; Qun Yang (BMC, 2019)
Abstract Background The dual-process theory is central to several models of addiction, implying the importance of automatic processes in the maintenance and development of addiction. Implicit beliefs are traces of previous experience which relate to the representation in cognition. Implicit behavioral tendencies are traces of previous experience which relate to the representation in behavioral tendencies. In this study, we aim to provide behavioral evidence for implicit beliefs and implicit behavioral tendencies towards smoking-related cues among Chinese male smokers and non-smokers. We also examine the relationships among implicit beliefs, implicit behavioral tendencies and smoking behaviors of smokers. Methods In order to achieve these goals, we used an implicit association test (IAT) to measure implicit beliefs and implicit behavioral tendencies simultaneously. Thirty-nine smokers and twenty-five non-smokers were tested, using smoking-related words and images, as well as neutral words and images as stimuli. Results Our analysis shows significant differences in smokers' and non-smokers' implicit beliefs and behavioral tendencies (t62 = 3.494, p < 0.001; t62 = 5.034, p < 0.001). In the group of smokers, implicit beliefs and implicit behavioral tendencies were positively correlated with each other (r = 0.460, p < 0.01). In addition, smokers' scores for implicit behavioral tendencies are negatively correlated with the number of cigarettes smoked per day (r = − 0.51, p < 0.001). Conclusions This study suggests that implicit beliefs and behavioral tendencies toward smoking-related cues vary significantly between Chinese male smokers and non-smokers. In addition, there is a positive correlation between implicit beliefs and behavioral tendencies within smokers. It also shows for the first time that the implicit behavioral tendencies are related to smoking behaviors. Our results may be considered as references for smoking cessation interventions focused on changes at the implicit level, and they provide a new perspective for measuring different dimensions of implicit attitudes by an IAT. This finding might promote the development of the network theory of implicit attitudes.